2015
DOI: 10.15517/aie.v15i2.18535
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ discourses on young lesbians in the portuguese school context

Abstract: Los contenidos de este artículo están bajo una licencia Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
4
0
5
Order By: Relevance
“…Social structures of this sort, such as the Gay-Straight Alliances found in the USA, are associated with higher levels of mental health and less victimization among GLB students (Saewyc, 2011). On a more proximal level, a qualitative study showed that Portuguese teachers manifest prejudiced attitudes toward sexual minorities, for instance, by perceiving gays and lesbians as individuals who have the reverse gender roles (Rodrigues, Brás, Cunha, Petiz, & Nogueira, 2015). Aditionally, teachers manifested that school contexts are prevalently homophobic, and recognized the need of training on sexual diversity (Rodrigues, et al, 2015).…”
Section: Family Relationships and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Social structures of this sort, such as the Gay-Straight Alliances found in the USA, are associated with higher levels of mental health and less victimization among GLB students (Saewyc, 2011). On a more proximal level, a qualitative study showed that Portuguese teachers manifest prejudiced attitudes toward sexual minorities, for instance, by perceiving gays and lesbians as individuals who have the reverse gender roles (Rodrigues, Brás, Cunha, Petiz, & Nogueira, 2015). Aditionally, teachers manifested that school contexts are prevalently homophobic, and recognized the need of training on sexual diversity (Rodrigues, et al, 2015).…”
Section: Family Relationships and Mental Healthmentioning
confidence: 99%
“…On a more proximal level, a qualitative study showed that Portuguese teachers manifest prejudiced attitudes toward sexual minorities, for instance, by perceiving gays and lesbians as individuals who have the reverse gender roles (Rodrigues, Brás, Cunha, Petiz, & Nogueira, 2015). Aditionally, teachers manifested that school contexts are prevalently homophobic, and recognized the need of training on sexual diversity (Rodrigues, et al, 2015). Portuguese teachers' involvement seems to be mainly characterized by neglect and inaction.…”
Section: Family Relationships and Mental Healthmentioning
confidence: 99%
“…Alguns estudos revelam que os/as profissionais da educação têm tido atitudes homofóbicas (BUTLER & BYRNE, 1992;CLARK, 2010;FONTAINE, 1997;FONTAINE, 1998;RODRIGUES ET AL., 2015;SEARS, 1992;TELLJOHANN & PRICE, 1993) e influenciam as próprias atitudes e comportamentos dos/as outros/as alunos/as (FONTAINE, 1997;SEARS, 1992) que os/as têm como modelos ou conselheiros/as. Contudo, embora este panorama de homofobia nas escolas seja já comprovado na literatura, a maioria das escolas não aborda a temática da homossexualidade, nem os preconceitos encontrados no corpo docente (CLARK, 2010;FONTAINE, 1998).…”
Section: Práticas Dos/as Profissionais Da Educação No Contexto Escolarunclassified
“…9, nº 1, pp. 55-71, 201555-71, 57 JOHNSON, 2002RICHARDSON, 2000aRODRIGUES et al, 2015). Algumas investigações mostram que existem discursos heterossexistas 6 , sexistas 7 e práticas de violência no local de trabalho, na escola e outras instituições sociais e que estes discursos e práticas estão significativamente correlacionados com o sofrimento, a depressão, e o suicídio de pessoas LGBT (ALMEIDA, 2010;BAGLEY, 2000;RAGINS, SINGH & CORNWELL, 2007;SMITH & INGRAM, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation